Q. 143.7( 3 Votes )

If <span lang="EN

Answer :

Given: x = and y =


To prove:


The formula to use:


Taking log of x -


log x = log


log x = 0.5 sin1(t) log a


Differentiating both sides w.r.t t, we get -



___(1)


Taking the log of y -


log y = log


log y = 0.5 cos1(t) log a


Differentiating both sides w.r.t t, we get -



___(2)


Now, Dividing equation 2 by 1,we get -




OR


Let, y = tan-1


Put x = tan β


y = tan-1


1 + tan2 β = sec2 β


y = tan-1


y = tan-1



y = tan-1


y = tan-1 (tan ) { tan-1(tan x) = x }


y = = tan-1x


Differentiating both sides -


{ }



Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses